OPTIMIZATION OF THE CROPPING PATTERN OF MAIN CEREALS AND IMPROVING WATER PRODUCTIVITY: APPLICATION OF THE WATER FOOTPRINT CONCEPT†. (15th July 2019) - Ramezani Etedali, Hadi; Ahmadaali, Khaled; Gorgin, Faraz; Ababaei, Behnam
ABSTRACT: Different components of water footprint (WF) (green, blue, grey and white) and WF volume (WFV) were estimated for three main cereal crops in Iran (wheat, barley and maize) in the main cereal‐producing provinces. In order to classify the selected provinces according to their corresponding WFVs, hierarchical cluster analysis (HCA) was applied for clustering the WFV of maize, barley and wheat in irrigated and rainfed conditions. Then, the linear programming (LP) technique was used to determine the optimal cultivated area for cereals in order to minimize the total national WFV in irrigated and rainfed lands. The WFV of wheat, barley and maize production in irrigated lands were estimated to be 25 100, 5980 and 4610 Mm 3 yr −1, respectively, under the current practice. The optimized values of WFV under irrigated conditions were 877, 338 and 374 Mm 3 yr −1 lower than the current values, implying nearly 3.5, 5.7 and 8.1% achievable reductions. The reduction in rainfed lands was estimated to be 332 Mm 3 yr −1 or 2.9% for wheat (from 11 300 to 11 000 Mm 3 year −1 ) and 338 Mm 3 yr −1 or 5.7% for barley (from 5950 to 5610 Mm 3 yr −1 ). The results show that by optimizing the cultivated area of the main cereals in Iran, 2, 210 Mm 3 yr −1 or 4.5% of the national WFV could be saved. © 2019 John Wiley & Sons, Ltd. RESUME: Différentes composantes de l'empreinte eau (WF) (vert, bleu, gris et blanc) et du volume WF (WFV) ont été estimées pour trois principales cultures céréalières en Iran (blé, orge et maïs) dans les principales provinces productrices de céréales. Afin de classer les provinces sélectionnées en fonction des WFV correspondantes, une analyse de groupe hiérarchique (HCA) a été appliquée pour regrouper le WFV du maïs, de l'orge et du blé dans des conditions irriguées et pluviales. Ensuite, la technique de programmation linéaire (LP) a été utilisée pour déterminer la superficie cultivée optimale pour les céréales afin de minimiser le WFV national total dans les terres irriguées et pluviales. Le WFV de la production de blé, d'orge et de maïs dans les terres irriguées a été estimée à 25 100, 5980 et 4610 Mm 3 an −1, selon la pratique actuelle. Les valeurs optimisées du WFV dans des conditions irriguées étaient inférieures de 877, 338 et 374 Mm 3 an −1 aux valeurs actuelles, ce qui implique des réductions réalisables de près de 3, 5, 5.7 et 8.1%. La réduction des superficies pluviales a été estimée à 332 Mm 3 an −1 ou 2.9% pour le blé (de 11 300 à 11 000 Mm 3 an −1 ) et à 338 Mm 3 an −1 ou 5.7% pour l'orge (de 5950 à 5610 Mm 3 an −1 ). Les résultats montrent qu'en optimisant la surface cultivée des principales céréales en Iran, 2210 Mm 3 par an −1, soit 4.5% de la WFV nationale, pourraient être économisés. © 2019 John Wiley & Sons, Ltd.